Laboratory Diagnosis of Lupus Anticoagulants - Chantarangkul, Veena; Tripodi, Armando; Clerici, Marigrazia; Bressi, Caterina; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2002)
Residual platelets in plasma are considered detrimental after freezing-thawing, as phospholipids released from ruptured platelets may quench lupus anticoagulants (LA). We aimed at assessing the effect of residual platelets after freezing-thawing plasmas tested with two procedures for LA. Blood from 52 patients suspected of having LA were centrifuged at 2,500 g. Plasmas were subdivided into 2 aliquots. One was filtered to remove residual platelets and both were frozen and stored at –70° C. Silica clotting time (SCT) at low and high phospholipid concentrations and Staclot® LA with and without Hexagonal phospholipids were performed on thawed plasmas. Plasmas were considered LA-positive when both SCT and Staclot® LA performed on filtered plasmas were diagnostic for LA. Forty-two of 52 plasmas fulfilled the diagnostic criteria and were retained for subsequent analysis. SCT on non-filtered plasmas was diagnostic for LA in 42 of 42 plasmas. Though the median (range) percentage correction recorded after phospholipids addition for filtered plasmas, i. e., 67% (36%-83%) was reduced to 54% (25%-81%) for non-filtered plasmas (p <0.001), it was still above the cut-off (i. e., 20.9%). Staclot® LA on non-filtered plasmas was diagnostic for LA in 42 of 42 plasmas. Though the median (range) clotting time difference recorded after phospholipid addition for filtered plasmas, i. e., 40.8 (10-103.5) s was reduced to 31.7 (2.8-88.8) s for non-filtered plasmas (p <0.001), it was still above the cut-off (i. e., 1.7 s). In conclusion, residual platelets do not affect the diagnostic efficacy of SCT and Staclot® LA. However, the fact that the percentage correction for SCT and the clotting time difference for Staclot® LA are reduced by residual platelets, suggests that weak LA may be lost upon freezing-thawing non-filtered plasmas.
Keywords: Lupus anticoagulant; standardization; screening; thrombophilia